The Interplay between Formal and Informal Training for Basic-Level Workers: Comparing Experiences in Canada and the United Kingdom - Maurice Taylor; Karen Evans; Alia Mohamed (Adult Education Research Conference, 2007)
This study investigated the types of formal and informal training activities of basic level employees using a qualitative multi-site case study research design. Seven programs from Canada and four programs from the North and South of England were chosen from small, medium and large businesses. The range of formal and informal training activities is described as well as a preliminary analysis of informal learning as both an activity and as a process for workers improving their literacy skills.